Substituted cysteine modification and protection indicates selective interactions of the anesthetic photolabel pTFD-di-iPr-BnOH with α+/β– and α+/γ– transmembrane subunit interfaces of synaptic GABAA receptors - Kieran Bhave; Stuart A. Forman (PLoS ONE, 2025)
Background General anesthesia induced by etomidate, barbiturates and propofol is associated with positive modulation of synaptic αβγ GABA A receptors, inhibitory hetero-pentameric ligand-gated ion channels formed from homologous subunits arranged β-α-β-α-γ around a central gated chloride channel. Approaches based on mutations, amino-acid level analysis of photolabel incorporation, and cryo-electron micrography (cryo-EM) all indicate that etomidate binds selectively in two outer transmembrane β+/α– inter-subunit sites per receptor. These approaches also reveal that the potent barbiturate photolabel R-mTFD-MPAB binds selectively in homologous sites formed at α+/β– and γ+/β– interfaces. The anesthetic photolabel, pTFD-di-iPr-BnOH, was proposed to bind selectively in α+/β– and α+/γ– homologs of the etomidate sites, based largely on functional analysis of only 5 point mutations in α1β3γ2L receptors. Methods To further test the interactions of receptor-bound pTFD-di-iPr-BnOH with outer transmembrane inter-subunit sites, we used voltage-clamp electrophysiology in substituted cysteine modification and protection (SCAMP) experiments at 8 residues located in the five homologous sites, focusing on α+ and γ– loci. Control SCAMP studies were performed using etomidate and R-mTFD-MPAB. Results Incorporation of single cysteine mutations (α1M236C, α1S280C, α1A291C, β3L231C, β3M286C, γ2I242C, γ2L246C, and γ2S301C) produced functional GABA-responsive receptors that retained sensitivity to pTFD-di-iPr-BnOH modulation and displayed increased GABA sensitivity following exposure to the covalent sulfhydryl modifier p-chloromercuribenzenesulfonate (pCMBS). In the presence of pTFD-di-iPr-BnOH, pCMBS modification effects were reduced (evidence of steric protection) in receptors with cysteine mutations in α+ , β–, and γ–, but not in α–, β+ , or γ+ interfacial loci. Protection patterns with etomidate and R-mTFD-MPAB mirrored prior results. Discussion SCAMP results further support the hypothesis that pTFD-di-iPr-BnOH binds selectively in α+/β– and α+/γ– interfacial sites that are homologs of the β+/α– etomidate sites.